2011
DOI: 10.1029/2010gc003353
|View full text |Cite
|
Sign up to set email alerts
|

A multitracer approach for characterizing interactions between shallow groundwater and the hydrothermal system in the Norris Geyser Basin area, Yellowstone National Park

Abstract: [1] Multiple environmental tracers are used to investigate age distribution, evolution, and mixing in local-to regional-scale groundwater circulation around the Norris Geyser Basin area in Yellowstone National Park. Springs ranging in temperature from 3°C to 90°C in the Norris Geyser Basin area were sampled for stable isotopes of hydrogen and oxygen, major and minor element chemistry, dissolved chlorofluorocarbons, and tritium. Groundwater near Norris Geyser Basin is comprised of two distinct systems: a shallo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 30 publications
1
42
0
Order By: Relevance
“…Isotopic studies indicate that geothermal waters have relatively long residence times, emerging at the surface hundreds, or possibly thousands of years after initial infiltration as meteoric waters (Pearson and Truesdell, 1978;Rye and Truesdell, 2007;Gardner et al, 2011). Gases may flow by different pathways on different timescales as they move from their sources toward the surface.…”
Section: Future Directions For Gas Studies At Yellowstonementioning
confidence: 97%
“…Isotopic studies indicate that geothermal waters have relatively long residence times, emerging at the surface hundreds, or possibly thousands of years after initial infiltration as meteoric waters (Pearson and Truesdell, 1978;Rye and Truesdell, 2007;Gardner et al, 2011). Gases may flow by different pathways on different timescales as they move from their sources toward the surface.…”
Section: Future Directions For Gas Studies At Yellowstonementioning
confidence: 97%
“…4a) that includes hypothetical mixing models often used to explain observed concentrations of environmental tracers (Solomon et al, 2010;Gardner et al, 2011b): the binary mixing model (BMM), which represents sampled water that is a mixture of two end members (i.e., modern and very old); an exponential mixing model (EMM), which represents sampled water that contains an exponential distribution of groundwater travel times; and, the piston flow model (PFM), which represents sampled water that has not mixed by hydrodynamic dispersion during transport.…”
Section: Cfcs and Sfmentioning
confidence: 99%
“…The robustness of this phenomenon and the mechanism by which CFC-12 could be removed in preference to the other trace gases remains to be established. A recent study of mixing between thermal and shallow groundwaters in Yellowstone National Park (Gardner et al, 2011) showed no consistent evidence for CFC-12 removal at higher concentrations, so the phenomenon may be restricted in occurrence to very low concentrations and/or type of thermal system.…”
Section: Thermal Effectsmentioning
confidence: 99%